Customer Discrimination: Evidence from Israel - Bar, Revital; Zussman, Asaf (Journal of Labor Economics, 2017)
This paper studies customer discrimination against Arab workers in the Israeli market for labor-intensive services. Relying on surveys, field data, and a natural experiment, we provide evidence consistent with Becker’s customer discrimination model. First, a significant share of Jewish customers prefer to receive labor-intensive services from firms employing Jewish rather than Arab workers; these preferences are most strongly linked to concerns for personal safety. Second, customer preferences affect firms’ hiring decisions. Third, firms employing Arab workers charge significantly lower service prices than those employing only Jewish workers.